Heritage Diplomacy of UNESCO in Post-Conflict Zones: the Case of Iraq - Serhii Orlov (Історико-політичні проблеми сучасного світу, 2025)
The article analyses UNESCO's activities in the context of heritage diplomacy in post-conflict Iraq. The purpose of the study is firstly to fill the scientific gaps in the understanding and conceptualisation of heritage diplomacy, and secondly to identify the peculiarities of UNESCO's use of heritage diplomacy in the post-conflict zone of Iraq. Thus, two main objectives were set: 1) to outline the understanding of the concept of "heritage diplomacy"; 2) to analyse UNESCO's activities in the context of heritage diplomacy in Iraq and its impact on intercultural relations. "Heritage diplomacy" is a relatively new concept that has an interdisciplinary nature. Through the synthesis of several approaches to this phenomenon, an attempt to define "heritage diplomacy" was made. Thus, heritage diplomacy can be defined as the use of the tangible, intangible, and natural pasts, manifested as heritage, as well as narratives about and around it, for political purposes, including the creation, strengthening, and promotion of a particular culture and/or intercultural relations. Then, an analysis of UNESCO's heritage diplomacy activities in Iraq was conducted. It shows that one of the defining peculiarities of UNESCO's heritage diplomacy is the focusing on one or several heritage objects and building a narrative around them. This particular type of heritage, which is the point of focus of the overall narrative, was called a "focal heritage". An interesting observation in the case of Mosul is at first the emphasis on Islamic sites, which was then balanced by the importance of Christian sites in light of improved interfaith relations, thus maintaining the commitment to the primary idea of rebuilding post-conflict Mosul through a narrative of ethnic and religious diversity. Also, the nature of UNESCO as a platform of promoting particular cultures through the UNESCO World Heritage, Tentative, and Intangible Cultural Heritage Lists was pointed out.